Evaluation of Aphrodisiac Activity of Siddha Herbal Formulation Vithu Vagai Chooranam in Experimental Rats (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Aphrodisiac agents are used to arouse sexual desire, sexual pleasure, or sexual behavior. Manysynthetic drugs are available in the market for improving sexual function. Even though modern medicinesare widely accessible, it has some ill effects. To combat these side effects, people turn to alternative medicalpractices to combat these side effects. In this regard, a study was performed to investigate the aphrodisiacpotential of herbal formulation Vithu vagaichooranam (VVC) by mating behavior study in male Wistarrats. Materials and Methods: The test drug VVC at 70 mg/kg and 90 mg/kg, Sildenafil citrate as Standard(5 mg/kg, p.o) and vehicle control (1 mL/kg p.o) were administered orally to rats (n = 6 animals per group) for14 days. On the 15th day, the sexual behavior of the experimental rats was observed in a dim light in speciallydesigned cages. The mating behavior parameter of male rats in each group was recorded individually. Results: Oraladministration of VVC at both doses significantly increased the frequencies of mount, intromission, ejaculationfrequency, Anogenital sniffing, and genital grooming (P < 0.001) when compared to the control and standarddrug. The latencies of mount and intromission were significantly reduced and ejaculation latency was prolonged.Conclusion: The results of the study strongly suggested that the VVC has significant aphrodisiac potential in theabove experimental model in male Wistar rats. Hence, in future, this formulation can be used as a potent stimulatorof sexual behavior and an alternative for various sexual dysfunctions. The results thus support the therapeuticactivity of this formulation claimed in the literature.